The Impact of Implementing Standard Operating Procedures and Supervision on Employee Performance - Shela Rahareng (BJRM (Bongaya Journal of Research in Management), 2021)
This study aims to examine and analyze the effect of implementing standard operating procedures and supervision on employee performance. This study uses primary data involving 84 respondents from the Regional Drinking Water Company (PDAM) employees in the Palu Branch Office. The research data was tested using the classical assumption test in normality assumptions, multicollinearity assumptions, and heteroscedasticity assumptions. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. The results showed that both partially and simultaneously applying SOPs and supervision had a positive and significant effect on employee performance, so that all proposed hypotheses were accepted.